MicroRNA181c inhibits prostate cancer cell growth and invasion by targeting multiple ERK signaling pathway components. Issue 5 (16th January 2018) - Su, Zhengzheng; Zhang, Mengni; Xu, Miao; Li, Xinglan; Tan, Junya; Xu, Yunyi; Pan, Xiuyi; Chen, Ni; Chen, Xueqin; Zhou, Qiao
Abstract : Background: The ERK signaling pathway is frequently deregulated in tumorigenesis, mostly by classical mechanisms such as gene mutation of its components (eg, RAS and RAF ). However, whether and how multiple key components of ERK pathway are regulated by microRNAs are not clear. Methods: We firstly predicted post‐transcriptional regulation of multiple key components of the ERK signaling pathway by miR181c through bioinformatics analysis, and then confirmed the post‐transcriptional regulation by dual luciferase reporter gene assays and Western blot analysis. The biological effects of miR181c on prostate cancer cell proliferation, apoptosis, migration, and invasion were measured by CCK‐8 assay, flow cytometry, wound scratch assay, transwell cell migration, and invasion assays. Results: miR181c post‐transcriptionally regulated multiple key members of the ERK signaling pathway, including extracellular signal‐regulated kinase 2 (ERK2), ribosomal S6 kinase 2 (RSK2), serum response factor (SRF), and FBJ murine osteosarcoma viral oncogene homolog (c‐Fos). Ectopic expression of miR181c mimics effectively suppressed prostate cancer cell proliferation, migration, and invasion, but promoted cell apoptosis. Furthermore, miR181c treatment combined with the multi‐kinase inhibitor sorafenib significantly enhanced these anti‐tumor effects. Conclusions: Downregulation of miR181c results in deregulated ERK signaling and promotes prostate cancer cell growth and metastasis.